Enforcement of Criminal Sanctions of Health Quarantine Law Trespasser in Indonesia - Rizkiana, Rina Elsa; Gerry, Michael (Indonesian Journal of Advocacy and Legal Services, 2022)
WHO stated there was an additional variants of the Corona virus that were more easily transmitted and resistant to vaccines. The Indonesian government required to prevent the entry of these variants into Indonesian territory. This prevention realized by implementing a quarantine policy which guided by Law Number 6 of 2018 on Health Quarantine. However, there is a gap between the number of violations and the low rate of case resolution. One of the causes is people's non-compliance with quarantine provisions after traveling abroad. This contradicted by the purpose of the Health Quarantine Act. This study aims to describe the legality and legal construction of the Health Quarantine Act formulation. This research was a normative juridical by using a statute approach and a conceptual approach. The results of the study indicate that violations of the Health Quarantine Act can be punish in order to provide certainty and law enforcement based on the ultimum remedium principle if they meet the provisions of the Health Quarantine Act. Thus, evaluation of legal content related to juridical consequences, and socialization as a persuasive effort and communication strategy need to be carried out so that transparency of legal consequences can be accepted and obeyed by the community.